Geographic and breed distribution of an Msp I PCR-RFLP in the bovine growth hormone (bGH) gene - Lagziel, A.S.; DeNise, S.; Hanotte, Olivier H.; Dhara, S.; Glazko, V.; Broadhead, A.; Davoli, R.; Russo, V.; Soller, M. (Wiley, 2000)
Information is presented on the frequency of the Msp I (-) allele in the third intron of the bovine growth hormone gene in a large number of cattle breeds. Consideration of the breed frequencies in relation to their geographic origin shows a low frequency for breeds originating in Northern Europe, moderate frequencies for breeds originating in Eastern Europe or the countries surrounding the Mediterranean basin, and very high frequencies for breeds originating in the Indian subcontinent. Consideration of breed frequencies in relation to breed type, shows low to moderate frequencies for the humpless breeds, high frequencies for the humped breeds. Various explanations for this distribution are discussed, among them the possibility that the Msp I (-) allele originated in the Bos indicus breeds of the Indian subcontinent, from which it diffused through the humpless Bos taurus breeds of Eastern Europe, the Mediterranean basin, eventually reaching Western, Northern Europe, Western Africa in low frequencies.